Linguagem visual e panos africanos: uma abordagem gráfica a partir de estampas - Martins, Edna [UNESP] (2014)
Considering that Brazil's population is made up of a significant number of African and Afro-descendants, the culture of these is amalgamated to Brazilian culture. Among Africans, the dress is equivalent to live. In this context the use of cloths as body coverings is very important, and the impregnated textile material typefaces expressing legends, myths, rules of social behavior, political, religious and others. Being African cloth important cultural vehicle, this research aims to identify which are the graphical components that appear most frequently on surfaces, specifically certain cloths like Adinkra, the Adire, the Bogolan, Gara and Kente, which They may be used for the development of Design and Fashion products available later in Brazilian markets. For that we used bibliographical research with study material acquired from books, theses, dissertations, journals, images, both the printed medium as electronic, with the aim of resuming concepts of elements of Visual Language, principles of Gestalt, Graphic Design, Surface Design, African fabrics, production and Crafts material, to achieve the aforementioned goal. This study was a bit beyond the original proposal reaching other specific points that could contribute to the development of Brazilian products aimed at African theme.